Assessing Patient Satisfaction with enhanced Recovery Surgery Protocol in Elective Cesarean Sections (CS) Deliveries - Sarwat Khalid, Sumera Mehmood, Asma Iqbal Ansari, Amna Begum, Asma Iqbal, Maryam Shahid, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This study aimed to explore patient satisfaction associated with the implementation ofEnhanced Recovery after Surgery (ERAS) protocols in women undergoing elective Cesarean Sections (CS).